Effects of Mg and Cu dopants on the properties of zinc oxide nanorod arrays / M.F. Malek ... [et al.]. - Muzaffar Shah, Malek; M.H., Mamat; A.S., Ismail; Mohammad Jafar, Salifairus; Z., Khusaimi; M., Rusop (2017)
We had successfully synthesised Mg-doped zinc oxide (MZO) and Cudoped zinc oxide (CZO) nanorod arrays (NRAs) on Al-doped ZnO (ZAO)-coated glass substrates using immersion method and investigated their structural properties. With the incorporation of the Mg dopant, the length and crystallinity of MZO NRAs is higher compared to that of the CZO NRAs. The average optical transmittance of MZO NRAs was slightly lower than that of the CZO NRAs over the visible wavelength region. With the incorporation of the Cu dopant, the morphology of the CZO sample was slightly different from that of the MZO NRAs. The CZO NRAs present granular with small sphere shape. On the other hand, the MZO NRAs exhibit a hexagonal shape structure with a flat-top facet. Rods with a diameter of 58.9-96.7 nm were uniformly grown on the ZAO-coated glass substrate.